INDIVIDUAL PERCEPTIONS OF PUBLIC SECTOR’S RISK CULTURE - Christiani, Maria Riche; Adhariani, Desi (Faculty of Economics and Business University of Mataram, 2025)
Effective risk management in the public sector is essential; however, individual perspectives reveal gaps in implementation and a weak risk culture, which increase the potential for errors, fraud, and corruption. This study evaluates individual perceptions that shape organizational culture to support effective risk management at Office B, a public service agency managing a significant budget. A qualitative case study approach was employed using method and data triangulation (document analysis, surveys, and interviews), based on frameworks from the Institute of Risk Management and Schein’s Organizational Culture Theory. The findings indicate that the risk culture is